What Workers Want - Haiven, Larry (Labour / Le Travail, 2002)
The article reviews the book, "What workers want," by Richard B. Freeman and Joel Rogers.
Keywords: Business And Economics--Labor And Industrial Relations; Employee involvement; Employees; Employers; History--History of North And South America; Job satisfaction; Labor unions; Manual workers; Participatory management; Polls & surveys